Identification and management of distributed data : NGN, content-centric networks, and the web - Bartolomeo, Giovanni, 1977- (CRC Press, Taylor & Francis Group, 2013)
"Preface The motivation behind this book was to provide students and future information engineers with a useful collection of Internet standards, technologies, and techniques that are derived from research projects for the management of distributed data. We wrote the book in a very exciting period of the Internet. The ubiquitous access of the Internet in daily life by all has allowed the emergence of new sorts of businesses, based on the staggering, and at times puzzling, amount of information on the Internet. Search engines, social networking, online advertising, and online commerce have been built on the aggregation and sharing of personal data. Carriers are closely cooperating with content providers to allow a deeper integration between their services and the underlying network, improving the quality of their customers' experience. Governments and public administrations have begun to simplify the way public data are accessed by opening their archives to citizens through the web. Although several academic courses are offered that discuss data management and networking, few of them focus on the convergence of networking and software technologies for identifying, addressing, and managing distributed data. This book focuses on this convergence-- a result of a series of long processes in the history of the Internet, in which data management has been thought and rethought many times"--